Inhibition of extracellular matrix production and remodeling by doxycycline in smooth muscle cells - Rogelio Palomino-Morales; Carolina Torres; Sonia Perales; Ana Linares; Maria Jose Alejandre (Elsevier, 2016)
Alterations in the extracellular matrix (ECM) production and remodeling of smooth muscle cells (SMCs) have been implicated in processes related to the differentiation in atherosclerosis. Due to the anti-atherosclerotic properties of the tetracyclines, we aimed to investigate whether cholesterol supplementation changes the effect of doxycycline over the ECM proteins synthesis and whether isoprenylated proteins and Rho A protein activation are affected. SMC primary culture isolated from chicks exposed to atherogenic factors in vivo (a cholesterol-rich diet, SMC-Ch), comparing it with control cultures isolated after a standard diet (SMC-C). After treatment with 20 nM doxycycline, [H3]-proline and [H3]-mevalonate incorporation were used to measure the synthesis of collagen and isoprenylated proteins, respectively. Real-time PCR was assessed to determine col1a2, col2a1, col3a1, fibronectin, and mmp2 gene expression and the pull-down technique was applied to determine the Rho A activation state. A higher synthesis of collagens and isoprenylated proteins in SMC-Ch than in SMC-C was determined showing that doxycycline inhibits ECM production and remodeling in both SMC types of cultures. Moreover, preliminary results about the effect of doxycycline on protein isoprenylation and Rho A protein activation led us to discuss the possibility that membrane G-protein activation pathways could mediate the molecular mechanism.